Comparison of the Effectiveness of Elderly Gymnastics with Neuromuscular Tapping on Dynamic Balance and Spinal Flexibility in the Elderly - Melur Belinda; Yuly Peristiowati; Siti Farida Noor Layla (STRADA : Jurnal Ilmiah Kesehatan, 2024)
The elderly experience changes in physiological function and body structure, including decreased muscle mass, and joint stiffness. These changes lead to a decrease in the functional balance of the body. This study aims to analyze the difference in the effect of elderly gymnastics and the combination of elderly gymnastics with neuromuscular taping on dynamic balance and flexibility of the elderly. The design of this study was a quasi-experiment with two groups: group 1 elderly gymnastics, while group 2 elderly gymnastics and neuromuscular taping. The study population was the elderly in Karanglo Indah Elderly Gymnastics Group Malang City aged 60-74 years.